The probably use of MR-spectroscopy and diffusion weighted-MRI of bone marrow for treatment monitoring in patients with chronic lymphatic leukemia - Vicente Martínez-Vega; Mar Jiménez-Peña; Javier Carrascoso-Arranz; Margarita Rubio-Alonso; Juan Bachiller-Egea; Carmen Martínez-Chamorro; Manuel Recio-Rodríguez (Annals of Bone Marrow Research - Peertechz Publications, 2021)
Objectives: To assess the usefulness of proton MR-spectroscopy (1H-MRS) and diffusion-weighted MRI (DW-MRI) sequences in the follow-up of CLL-patients with chemotherapy treatment. The monitoring of CLL-patients susceptible to chemotherapy treatment is complicated due to the difficulty in assessing the response to treatment. Chemotherapy leads to changes in bone marrow composition and these changes can be evaluated by functional MR-sequences.  Methods: 23 patients diagnosed with CLL by our hospital's Hematology Service underwent a lumbar MR prior and post-chemotherapy applying 1H-MRS and DW-MRI. The concentrations of water and lipids were quantified applying the quantification program LCModel. The Apparent Diffusion Coefficient (ADC) values were calculated with the Functool program (GE). The Wilcoxon sign test was used to compare pre and post treatment results, considering statistically significant P values lower than 0.05.  Results: Responder patients decreased the ratio H2O/lipids concentration measured with 1H-MRS and increased the ADC value on DW-MRI in post-treatment studies (P<0.05). Patients without response increased the ratio and decreased the ADC values or did not modify the data. Conclusion: 1H-MRS and DW-MRI of spinal bone marrow are non-invasive and repeatable techniques that might help in follow-up monitoring of patients with CLL.